Prevalence and correlates of HIV infection among men who inject drugs in a remote area of Vietnam - Van T. Nghiem; Thanh C. Bui; Patrick P. Nadol; Son H. Phan; Binh T. Kieu; Ryan Kling; Theodore M. Hammett (BMC, 2018)
Abstract Background Lack of information on the HIV epidemic among men who inject drugs (MWID) in northwestern Vietnam, a remote area, may hamper national efforts to control the disease. We examined HIV prevalence, needle-syringe sharing behaviors, and associated factors among MWID in three areas of northwestern Vietnam. Methods We used descriptive analysis to report the characteristics, frequency of risk behaviors, and of access to healthcare services among the MWID. Univariable logistic regression was used to assess the associations between the HIV infection, needle-syringe sharing behaviors, and their independent variables. We further explored these associations in multivariable analyses where we included independent variables based on a priori knowledge and their associations with the dependent variables determined in univariable analyses (p <  0.25). Results The HIV prevalence was 37.9, 16.9, and 18.5% for Tuan Giao, Bat Xat, and Lao Cai City, respectively, and 25.4% overall. MWID of Thai minority ethnicity were more likely to be HIV-positive (adjusted odds ratio (AOR) 3.55; 95% confidence interval (CI) 1.84-6.87). The rate of needle-syringe sharing in the previous 6 months was approximately 9% among the MWID in Tuan Giao and Lao Cai City, and 27.8% in Bat Xat. Two thirds of the participants never underwent HIV testing before this study. Ever having been tested for HIV before this study was not associated with any needle-syringe sharing behaviors. Among the HIV-positive MWID, those who received free clean needles and syringes were less likely to give used needles and syringes to peers (AOR 0.21; 95% CI 0.06-0.79). Going to a "hotspot" in the previous week was associated with increased odds of needle-syringe sharing in multiple subgroups. Conclusion Our findings on HIV prevalence and testing participation among a subset of MWID in the northwestern Vietnam were corroborated with trend analysis results from the most recent HIV/STI Integrated Biological and Behavioral Surveillance report (data last collected in 2013.) We provided important insights into these MWID's risky injection behaviors. We suggest heightened emphasis on HIV testing and needle and syringe provision for this population. Also, policymakers and program implementers should target hotspots as a main venue to tackle HIV epidemics.